2010
DOI: 10.1103/physrevlett.105.220404
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Red-Blue Detuning Asymmetry in Matter-Wave Superradiance

Abstract: We report the first experimental observations of strong suppression of matter-wave superradiance using blue-detuned pump light and demonstrate a pump-laser detuning asymmetry in the collective atomic recoil motion. In contrast to all previous theoretical frameworks, which predict that the process should be symmetric with respect to the sign of the pump-laser detuning, we find that for condensates the symmetry is broken. With high condensate densities and red-detuned light, the familiar distinctive multi-order,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…and, as a result, a complex nomenclature has evolved including the terms superradiance, superfluorescence, amplified spontaneous emission, mirrorless lasing, and random lasing [2, 4,[6][7][8][9], the distinctions among which we will not attempt to summarize here. The problem has recently seen renewed interest in the field of cold atoms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This is partly because cold atoms provide a reproducible, easily characterized ensemble in which Doppler broadening effects are small and relaxation is generally limited to spontaneous emission.…”
mentioning
confidence: 99%
“…and, as a result, a complex nomenclature has evolved including the terms superradiance, superfluorescence, amplified spontaneous emission, mirrorless lasing, and random lasing [2, 4,[6][7][8][9], the distinctions among which we will not attempt to summarize here. The problem has recently seen renewed interest in the field of cold atoms [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This is partly because cold atoms provide a reproducible, easily characterized ensemble in which Doppler broadening effects are small and relaxation is generally limited to spontaneous emission.…”
mentioning
confidence: 99%
“…The quantum phase transition (QPT) [20] from the normal phase to the superradiance phase in BECs-cavity system has been observed experimentally [21][22][23]. In the experiment [23], the two-level atoms induce a sufficiently strong coupling between the transverse pump light and the cavity field, which is a nonlinear interaction and the system undergoes a phase transition when tuning the power of the transverse pump light.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the wave-function of the ground state shall take the Thomas-Fermi form in mean-field approximation because of the presence of the atomic interactions. The superradiance of such symmetric BEC has been studied [1][2][3][4][5][6][7][8][9]; however, research of that for the asymmetric BEC as that shown in Fig. 2(a) has been lack.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…Ever since the first observation of superradiant scattering from the BEC, a series of experiments [1][2][3][4][5][6][7][8][9] have been explored to simulate the origin of this phenomenon and the dynamical properties of the light-atom coupling process. Experiments of different geometries, such as the Rayleigh and Raman superradiant scattering, in which the lights are pumped in the axial or radial direction [10,11] were intensively studied.…”
Section: Introductionmentioning
confidence: 99%